(untitled) (Mwanga wa Lugha, 2021)
This study seeks to highlight the phenomenon of pragmatic mislay in translation of hedges in presidential political speeches from English to Kiswahili and Vice versa. Hedges are considered an additional ingredient in communication, making the interlocutor to pass his or her message either elaborately or implicitly Lakoff, (1973). Information may pragmatically be expressed in an explicit or implicit manner to amplify or to conceal a specific message through usage of hedging devices which are not forthrightly detectable in a statement. This pragmatic function in a statement is bound to be missed out in translation leading to pragmatic mislay on the speeches owing to the fact that, hedging is a political strategy of communication for myriads of reasons. This is detectable in culture specific terms found in the proverbs often used by the politicians in their public addresses to convince and alter the thinking process of a community and sway them to vote in a certain direction. The study focused on cultural-specific terms in certain proverbs used by politicians and their translatability as hedging devices. Kiswahili and English are the official languages and as such used interchangeably by politicians in political rallies. Due to their polygramatic nature, the hedging devices in the political language are a problem in translation. This would establish the connecting factor between pragmatics and translation.